Readiness of Warunggunung Village, Lebak Regency in Realizing the Smart Village Program: a Review of the Smart Government Domain - Ramadhan, Rika; Priyadi, Budi Puspo; Astusi, Retno Sunu (Journal La Sociale, 2024)
In research This the existence of a Smart village in Warunggunung Village can understand problems faced by the village with understand situation latest from problems that exist in the village, with manage various source power to be effective and efficient, then maximizing objective for serve public. Study This aim for see how one dimensions of the smart village implemented namely smart government in Warunggunung Village, Lebak Regency. Method used in study This is descriptive qualitative use theory from Bakri (2004) about readiness with the STOPE model. Interview data collection done with informant from the Warunggunung Village Head's Office and parties public. Research result show that readiness village warunggunung in dimensions of smart government yet walk with Good seen from lack of budget and HR readiness of Warunggunung Village in prepare digitalization service village in Warunggung Village Because Still There is a number of features that are not yet Can walk optimally. Other perceived obstacles were also seen from side public it's the one that’s lacking participate active and public with the world of digitalization. Efforts made as preparedness and coping factor inhibitor with do training For increase the quality of human resources as well Keep going do socialization massively to the people of Warunggung Village about method use technology digital information and services.